Evaluating the Feasibility of Web-Monitoring Methodology for Measuring Exposure to Online Cancer Misinformation - Cindy A Turner; Andy J King; Ida Tovar; Morgan M Millar; Rachel R Codden; Jia-Wen Guo; Skyler Johnson; Anne C Kirchhoff; Margaret Raber; Xiaoming Sheng; Deanna Kepka; Echo L Warner (JMIR Cancer)
AbstractUnderstanding the impact of online cancer misinformation exposure on health outcomes is an area of growing concern, but few methods exist to objectively measure this exposure. The primary aim of this paper is to describe the lessons learned in using web-monitoring software to measure exposure to online cancer misinformation among patients with cancer. These lessons learned emerged from our experience conducting a prospective pilot study from October 2022 to August 2023 wherein we adopted commercially available web-monitoring software to capture cancer-related web content. A total of 56 patients with cancer completed a baseline survey, and 17 of these participants installed web-monitoring software on their personal computer for 30 days and completed a follow-up survey. We use implementation outcomes to describe the feasibility of this methodological approach using lessons learned in 3 topic areas, namely data quality, software implementation, and participant acceptability. We found the web-monitoring data to be appropriate for our research aim to objectively measure cancer misinformation exposure, although compatibility issues with social media websites and mobile devices negatively impacted data quality. A complex installation process negatively impacted implementation and caused an unknown number of participants to drop out after the baseline survey. Among participants who completed the study, reported acceptability of web-monitoring software for research purposes was high, though potentially biased by selective retention. This pilot study testing web-monitoring software for research purposes among patients with cancer demonstrates high acceptability but low feasibility due to implementation barriers. We propose practical solutions to address these barriers and believe the lessons learned here offer a promising foundation for improving methods to objectively measure patient exposure to online cancer information. Future studies should focus on exploring perceptions of web-monitoring among nonparticipants, considering alternative approaches, and expanding web-monitoring to include mobile devices.